2020
DOI: 10.1002/bkcs.11991
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Level Investigation of Oil Sludge at the Bottom of Oil Tank in Ratawi Oil Field by Atmospheric Pressure Photo Ionization Ultrahigh‐resolution Mass Spectrometry

Abstract: The crude oil precipitate recovered from the bottom of oil tanks in the Ratawi oil field is analyzed by positive mode atmospheric pressure photoionization ultrahigh-resolution mass spectrometry (APPI UHR-MS). The precipitate is fractionated into three fractions and according to the APPI UHR-MS data, the mass spectrum of the top fraction is similar to that of the original oil while the middle fraction shows the lowest M n and m/z distribution. The data obtained with APPI technique show that hydrocarbon molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…70,105,106 Kim and co-workers applied (+) APPI UHR-MS to study the transformation of hazardous or toxic components in weathered and photodegraded oils, 19,107 the chemistry of diesel oil, 108 and the formation of oil sludge. 109 In the latter study, (+)-APPI FT-ICR MS was used to study the detailed chemical composition of oil sludge (solid deposits from an oil tank) collected from the bottom of an oil tank in the Ratawi oil field in Iraq. The APPI MS results for the three fractions of the oil sludge suggested that aromatic compounds with long alkyl chains were mainly responsible for sludge formation (Figure 2).…”
Section: Apci Ms and Appi Msmentioning
confidence: 99%
See 2 more Smart Citations
“…70,105,106 Kim and co-workers applied (+) APPI UHR-MS to study the transformation of hazardous or toxic components in weathered and photodegraded oils, 19,107 the chemistry of diesel oil, 108 and the formation of oil sludge. 109 In the latter study, (+)-APPI FT-ICR MS was used to study the detailed chemical composition of oil sludge (solid deposits from an oil tank) collected from the bottom of an oil tank in the Ratawi oil field in Iraq. The APPI MS results for the three fractions of the oil sludge suggested that aromatic compounds with long alkyl chains were mainly responsible for sludge formation (Figure 2).…”
Section: Apci Ms and Appi Msmentioning
confidence: 99%
“…The performance of APCI/APPI FT‐ICR MS methods in characterizing NOM and petroleum compounds has been reported 70,105,106 . Kim and co‐workers applied (+) APPI UHR‐MS to study the transformation of hazardous or toxic components in weathered and photodegraded oils, 19,107 the chemistry of diesel oil, 108 and the formation of oil sludge 109 . In the latter study, (+)‐APPI FT‐ICR MS was used to study the detailed chemical composition of oil sludge (solid deposits from an oil tank) collected from the bottom of an oil tank in the Ratawi oil field in Iraq.…”
Section: Analysis Of Petroleum‐nom By Uhr‐ms Coupled With Different I...mentioning
confidence: 99%
See 1 more Smart Citation
“…A versatile tool for the non-targeted soil analysis is ultrahigh resolution Fourier transform mass spectrometry (FTMS) 21 in combination with different atmospheric pressure ionization (API) methods, such as electrospray ionization (ESI), atmospheric pressure chemical ionization (APCI), atmospheric pressure photo ionization (APPI) 22,23 and atmospheric pressure laser ionization (APLI), in negative and positive mode. This delivers multidimensional information about naphthenic type compounds 24,25 or different polyaromatic compounds in ultracomplex samples such as crude oil 26,27 and soil. 28,29 Negative mode ESI FTMS analysis of dissolved organic matter (DOM) [30][31][32][33][34] or soil organic matter (SOM) [35][36][37] helped to understand the soil biogeochemistry and global carbon cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, gas chromatography/mass spectrometry (GC/MS) has been used to determine elemental sulfur in naphtha and gasoline, gel permeation chromatography (GPC) and ultrahigh resolution mass spectrometry have been successfully applied in the characterization of aromatic hydrocarbons and sulfur heterocycles in a heavy crude oil, while recently the analysis of three classes of sulfur compounds has been shown by using LC separation and an online detection and quantification by ICP-MS . High-resolution mass spectrometry (HRMS) is the method of choice for the investigation of complex mixtures due to its ability to provide high resolving power and highly accurate mass measurements. Electrospray ionization (ESI) is not commonly selected for the ionization of polycyclic aromatic sulfur hydrocarbons (PASHs) since these species are typically not basic enough to be easily protonated and this method is often used for acidic types of compounds. Thus, atmospheric pressure photoionization (APPI) is preferably used for their ionization. However, using chemical methods such as alkylation, we can achieve a selectivity toward sulfur-containing species, producing preformed ions and thus making their characterization by ESI possible .…”
Section: Introductionmentioning
confidence: 99%